2004
DOI: 10.1523/jneurosci.3715-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Netrin Receptor Binding Reveals Domains of Unc5 Regulating Its Tyrosine Phosphorylation

Abstract: Netrin and its receptors Unc5 and deleted in colorectal carcinoma (DCC) regulate axon guidance and cell migration. We defined domains involved in the interactions between netrin-1, DCC, and Unc5c. We show that Unc5 requires both Ig domains to interact with netrin. DCC binds through the fourth fibronectin type III domain, whereas netrin binds through multiple domains to both receptors. We examined the functional consequences of removing the netrin binding and nonbinding domains from Unc5 in vitro and in vivo. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 27 publications
7
70
0
1
Order By: Relevance
“…DCC-4Fbn is the 4 th fibronectin domain of DCC ectodomain (Fig. 3A) and has been shown to interact with netrin-1 (18). To confirm the DCC-4Fbn/netrin-1 interaction, an ELISA was performed coating DCC-4Fbn and revealing a possible interaction with increased concentrations of either netrin-1 or netrin-4.…”
Section: Resultsmentioning
confidence: 99%
“…DCC-4Fbn is the 4 th fibronectin domain of DCC ectodomain (Fig. 3A) and has been shown to interact with netrin-1 (18). To confirm the DCC-4Fbn/netrin-1 interaction, an ELISA was performed coating DCC-4Fbn and revealing a possible interaction with increased concentrations of either netrin-1 or netrin-4.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, it has been reported that the removal of the netrin binding second Ig domains of UNC5C caused an increase of UNC5C in the basal tyrosine phosphorylation, occurring during melanoma progression at the stage when cells first become competent for metastasis. 79,80) ZNF146 or human OZF gene, located in chromosome band 19q13.1, is overexpressed in the majority of pancreatic cancers with more than 80% of colorectal cancers. [44][45][46] ZNF146 encoding protein consisted of ten Kruppel zinc finger motifs, called zinc finger protein OZF.…”
Section: Discussionmentioning
confidence: 99%
“…Constructs and Reagents-Plasmids encoding the full-length human DSCAM-Flag, DSCAM⌬N, DSCAM⌬C, the full-length human UNC5C-HA and UNC5C truncation mutants (⌬Ig1, ⌬Ig2, ⌬Igs, ⌬TSP) have been described previously (21,38). The targeted sequences of DSCAM shRNA, control DSCAM shRNA, UNC5C shRNA, and control UNC5C shRNA are: 5Ј-AAAGAGTTTAGCTGAAATGCT-3Ј (DSCAM shRNA), 5Ј-AATGCATCTCTGCAAGAGGTA-3Ј (control DSCAM shRNA), 5Ј-AAGAACCCAAGGCTCTTCATT-3Ј (UNC5C shRNA) and 5Ј-AACTGTACTGTGTCAGAGGAA-3Ј (control UNC5C shRNA).…”
Section: Methodsmentioning
confidence: 99%